PENGARUH KOMITMEN ORGANISASI, MOTIVASI BERPRESTASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT WANGSA JATRA LESTARI - Restu Adi Nugroho; Sri Hartono; Sudarwati . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2016)
This study aimed to analyze 1) to determine the influence of organizational commitment on employee performance PT Wangsa Jatra Lestari. 2) to determine the influence of achievement motivation on employee performance PT Wangsa Jatra Lestari. 3) to determine the influence of leadership style on employee performance PT Wangsa Jatra Lestari. 4) to determine the influence of organizational commitment, achievement motivation and leadership style simultaneously to employee performance PT Wangsa Jatra Lestari.Population of this study are employees of PT Wangsa Jatra Lestari which totaling 200 employees. In this study sample was taken 30% of the population that is 60 respondents. Data collection techniques in this study using questionnaires. Techniques of data analysis in this study are multiple linear regression analysis, t-test, F-test and the coefficient of determination with the help of SPSS version 23 . Keywords: organizatioal commitment, achievement motivation, leadership style and employee performance